Composite fibrous membrane comprising PLA and PCL fibers for biomedical application. (October 2022) - Zhang, Siyi; Yan, Dan; Zhao, Lifang; Lin, Jinyou
Abstract: Great effort has been devoted to investigating the biodegradable composite fibrous membranes (CFM) comprising polymer blends in single fiber via electrospinning. However, the fibrous membrane scaffolds consisting of two kinds of electrospun fibers were seldom presented for biomedical application. In this study, CFM composed of poly(lactic acid) and polycaprolactone fibers with different rations were fabricated via multi-spinnerets blended electrospinning. The morphological structures, composition, wetting behaviors and mechanical properties of as-prepared CFM were investigated. The CFM, mimicking native tissues with interconnected and porous surfaces, for biomedical application was comprehensively evaluated. The results showed that cells phenotypes did not change significantly on these CFM and did not present inflammatory responses. Cells could proliferate well on these scaffolds, suggesting their good biocompatibility. Thus, the as-prepared CFM could be designed to adapt different requirements in tissues engineering by changing fiber ratios according to polymer intrinsic properties, presenting their synergistic advanced features. Graphical abstract: Image 1 Highlights: The nanofibrous scaffolds were prepared by multi-spinnerets blended electrospinning. The relative amount of polymers in nanofibrous scaffolds can be finely modulated. The nanofibrous scaffolds exhibit cytocompatibility and non-toxicity to cells.